Columnar self-assembly in electron-deficient heterotriangulenes - Kivala, Milan; Pisula, Wojciech; Wang, Suhao; Mavrinskiy, Alexey; Gisselbrecht, Jean-Paul; Feng, Xinliang; Muellen, Klaus (Chemistry - A European Journal, 2013)
A series of soluble carbonyl-bridged heterotriangulenes, in which flexible n-dodecyl chains are attached through different spacers to the planar nitrogen-centered polycyclic core, have been synthesized. The introduction of triisopropylsilylethynyl moieties enabled, for the first time, the characterization of single-crystal columnar packing of a substituted heterotriangulene by X-ray crystallography. Electrochemical studies disclosed the carbonyl-bridged heterotriangulene core as a reasonably strong acceptor for a reversible two-electron transfer. The tendency of substituted heterotriangulenes to self-assemble in solution, on surfaces, and in the bulk appeared to sensitively depend on the nature of the lateral substituents, their steric demand, and the applied solution processing conditions. It can be concluded that 1) additional phenylene moieties between the heterotriangulene core and the n-dodecyl chains facilitate self-assembly by extending the π-conjugated polycyclic disc, 2) the rod-like ethynylene spacers introduce some additional flexibility and hence lower the overall aggregation tendency, and 3) the combination of both features in the phenylene-ethynylene moieties induces thermotropic liquid crystallinity. Playing the triangle: A series of electron-deficient heterotriangulenes with pendant alkyl chains has been synthesized and their propensity for self-assembly in solution, on a surface, and in the bulk was studied (see figure). A pronounced dependence of the self-assembly behavior on the nature of the spacer between the rigid heterotriangulene core and the flexible alkyl chains was identified. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrochemistry; heterotriangulenes; liquid crystals; polycyclic aromatic hydrocarbons; self-assembly